Effect of Health Education Demonstration Method and Leaflet Media about Consciousness on Knowledge and Attitude of Hormonal KB Acceptors - Sri Mulyati; Winancy Winancy (Poltekkes Kemenkes Jakarta III, 2019)
Breast cancer is a disease with characterized by uncontrolled development of cells and breast tissue. Women who has to use acceptors Hormonal contraception (Hormonal KB) has a risk of developing breast cancer. Self Breast Examination (BSE) or Periksa Payudara Sendiri (SADARI) is one of the easier and more efficient ways to be able to detect breast abnormalities by yourself. The purpose of the study was to determine the effect of health education by demonstration methods and leaflet media on breast self-examination of the knowledge and attitudes of WUS hormonal family planning acceptors about SADARI. This study was a quasi experiment: pretest-posttest design. The population was divided into 3 groups, namely groups given health education with leaflets, with demonstration methods, and a combination of leaflets + demonstrations. The results showed that the knowledge and attitudes of respondents before and after health education with leaflet media, demonstration methods, and leaflet + demonstration media combinations experienced a significant increase with a value of p <0.05 (p = 0,000). The increase score in the value of the average rating of knowledge was statistically significant in the demonstration group better than the leaflet group. The difference in the average value of the demonstration and demonstration group rankings + leaflets is not meaningful.